The gas of Camisea: geology, economy and uses - Zavala, Abel Andrés (2007)
The gas of Camisea is located in the Convención Cusco, its geology was developed in a basin of 3000 m of clásticos, from the Ordovísico to the Tertiary, conforming the Locations of Cashiriari and San Martin, with rocks, reservorios in Vivian, Chonta, Nia and others; being their components the explotation, transport and distribution of gas. In the economic fi eld the investment overcomes the US$1600 millions and has brought economic benefi ts for our country, with increments in the PBI 0.8% on the average, it overcame the US$4000 millions among the 2000 - 2006 and the would surpass long term US$11000 millions (2007 - 2033). Their main markets are the electric generation (60%) and the industry (40%). The gas of Camisea is a clean energy and non pollutant because it is inherently a fuel effi cient and of smaller cost in comparison with other fossil fuels.